Case Report: In Situ Expression of a Proliferation-Inducing Ligand in Neuromyelitis Optica - Baert, Laurie; Marignier, Romain; Lassmann, Hans P.; Huard, Bertrand (Frontiers in Neurology, 2021)
A proliferation inducing ligand (APRIL) mediates a key role in the generation and survival of antibody-inducing plasmocytes. Based on this, APRIL has been targeted in autoimmune diseases including multiple sclerosis (MS) and optic neuritis (ON). In MS lesions, APRIL has a new cellular target, the reactive astrocyte and mediates an immunosuppressive activity. Here, we analyzed APRIL expression in a case of neuromyelitis optica (NMO), another autoimmune neurodegenerative disease, showing selective aquaporin-4 depletion in the spinal cord, complement deposition and infiltration of polymorphonuclear cells. We analyzed by immunohistochemistry the presence of APRIL-producing cells, plasmocytes, astrocytes and the localization of secreted APRIL in a lesion from NMO. Plasmocytes were present close to APRIL-producing cells in meninges. However, our main observation was that APRIL targets reactive astrocytes in this lesion of NMO similarly to MS.